ANALISIS HARGA POKOK PRODUKSI DENGAN PENDEKATAN ACTIVITY BASED COSTING PADA UKM RANDUSARI DI BANJARREJO KABUPATEN LAMPUNG TIMUR - Suryadi Suryadi (Universitas Muhammadiyah Metro Lampung, 2018)
AbstractBased on the fact system in the business field of Randusari Banjarrejo UKM, East Lampung, it still uses a conventional or full costing system in which the cost of production is determined by collecting all of the expenditures that have been spent during the production process and dividing it to the amount of output produced. Therefore it raises the question of how much the cost of production is right and efficient for the products of Randusari Banjarejo UKM in East Lampung in accordance with the conditions in the field by using Activity Based Costing systems. For calculations with the activity based costing system itself has never been tried or examined so research needs to be conducted to analyze the determination of the cost of production based on the history of the use of raw materials and supporting materials in the Randusari Banjarrejo UKM in East Lampung.The method used in this study is the tabulation method with the help of software Microsoft Excel 2010. The data obtained in the form of both primary and secondary data is compiled and simplified and presented in tabulation form. The analytical method used is qualitative and quantitative methods. Analysis of cost of production using the activity based costing method. The results of the research on the cost of production of kapok mattresses by using an activity based costing system resulted in lower cost of production compared to the cost of production using a company system and the cost of producing foam mattresses with a system using an activity based costing system resulting in lower cost of production compared to principal prices production using a company system. Keywords: UKM, Production Cost, Activity Based Costing